2021
DOI: 10.1108/crr-06-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

Towards enhancing creativity in university settings: does hope of academic knowledge workers matter?

Abstract: PurposeAlthough a burgeoning body of literature has established the influence of hope and employee creativity, the debate on the relative importance of hope and its components of pathway and agency on its outcomes has not been clarified. Literature has it that hope and its individual components of pathway and agency have a varying magnitude of influence on its outcomes. Some scholars argue that agency and pathway components better predict its outcomes than overall hope. The current study establishes the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Studies have revealed that high-hope individuals possess several attributes that make them more satisfied. These include more creativity (Namono et al, 2021) [38], more persistence in pursuing their goals (Gallagher et al, 2017) [39], more ability to see opportunities and ways to achieve their desired goals (Pleeging et al, 2021) [18], and more resilience when facing negative situations (Arampatzi et al, 2020) [40]. Studies have shown that positive emotions can lead to both hope cognitions (agency and pathways thinking) (Ciarrochi et al, 2015 [41]) that might improve psychological outcomes (e.g., life satisfaction) by building hope agency and/or expanding hope pathways through broadening an individual's thought-action repertoire.…”
Section: Positive Emotions Hope and Life Satisfaction: Application Of...mentioning
confidence: 99%
“…Studies have revealed that high-hope individuals possess several attributes that make them more satisfied. These include more creativity (Namono et al, 2021) [38], more persistence in pursuing their goals (Gallagher et al, 2017) [39], more ability to see opportunities and ways to achieve their desired goals (Pleeging et al, 2021) [18], and more resilience when facing negative situations (Arampatzi et al, 2020) [40]. Studies have shown that positive emotions can lead to both hope cognitions (agency and pathways thinking) (Ciarrochi et al, 2015 [41]) that might improve psychological outcomes (e.g., life satisfaction) by building hope agency and/or expanding hope pathways through broadening an individual's thought-action repertoire.…”
Section: Positive Emotions Hope and Life Satisfaction: Application Of...mentioning
confidence: 99%